Macro, Trace and Toxic Element Composition in Liver and Meat of Broiler Chicken Associated with Cecal Microbiome Community - Dmitry Deryabin; Dianna Kosyan; Ludmila Vlasenko; Christina Lazebnik; Alexander Zatevalov; Ilshat Karimov; Galimzhan Duskaev (Biology)
The current study presents a meta-analysis of the detailed relationship between the composition of 25 essential and toxic elements in chicken tissues examined by ICP-MS and the gut microbial community analyzed using NGS techniques. The examination of chicken liver and meat revealed typical elemental compositions, called the “elementomes”. The α-elementomes showed high contents of macro elements (Na, K, Mg, Ca, P), majority trace elements (Sr, Se, Mn, Fe, Co, Cu, Zn) and some toxic elements (B, Pb, Ni, Cd); β-elementomes indicated accumulation of Si, V and Cr; γ-elementomes indicated accumulation of Al, As and Hg. Characterization of the microbiomes’ structure showed two distinct enterotypes, designated “microbiome patterns”; the first was enriched in the phylum Bacteroidota, and the second was dominated by Bacillota and coupled with members of the phyla Actinomycetota, Cyanobacteriota and Thermodesulfobacteriota. A comparison of elementomes and microbiomes demonstrated a clear correspondence between the α- and γ-elementomes belonging to the Bacteroidota-enriched pattern, while the β-elementome was predominantly found in chicken groups belonging to the Bacillota + ACT pattern. This insight proposes a novel strategy to improve deficiency or excess of certain elements in the host by gut microbiome modulation, which needs to be verified with further in vivo experiments.